2016
DOI: 10.1111/ggi.12712
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in depressive effects of experiencing spousal bereavement

Abstract: Aim Spousal death is a significant event that becomes a turning point in an individual's life. Widowed persons experience new circumstances, which might induce depression. However, the effects of spousal death on depression can differ by sex and culture. Thus, the present study examined the association between depressive levels and experience of spousal death in Korean adults aged older than 45 years. Methods The data were from the Korean Longitudinal Study of Aging from 2010 to 2012. The analysis used frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The average prevalence of depressive symptoms among Japanese older adults was 28.6% in 2010 and 21.3% in 2016 ( 22 ). Because many older people must care for a spouse who is ill ( 38 ), are transitioning to retirement ( 46 ), or have experienced the death of a spouse ( 47 ), these individuals can easily become depressed. We found that Chinese older people who were women, living in rural areas, unmarried/divorced/widowed, living alone, or who had poor self-perceived health and more than two chronic diseases were more likely to be depressed, which is in line with other studies ( 6 , 21 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…The average prevalence of depressive symptoms among Japanese older adults was 28.6% in 2010 and 21.3% in 2016 ( 22 ). Because many older people must care for a spouse who is ill ( 38 ), are transitioning to retirement ( 46 ), or have experienced the death of a spouse ( 47 ), these individuals can easily become depressed. We found that Chinese older people who were women, living in rural areas, unmarried/divorced/widowed, living alone, or who had poor self-perceived health and more than two chronic diseases were more likely to be depressed, which is in line with other studies ( 6 , 21 , 23 ).…”
Section: Discussionmentioning
confidence: 99%